2011
DOI: 10.1021/jp202322n
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Naphthoquinone Radical Anions by Electrospray Ionization: Solution, Gas-Phase, and Computational Chemistry Studies

Abstract: Radical anions are present in several chemical processes, and understanding the reactivity of these species may be described by their thermodynamic properties. Over the last years, the formation of radical ions in the gas phase has been an important issue concerning electrospray ionization mass spectrometry studies. In this work, we report on the generation of radical anions of quinonoid compounds (Q) by electrospray ionization mass spectrometry. The balance between radical anion formation and the deprotonated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 53 publications
1
42
0
1
Order By: Relevance
“…The classes of organic compounds include polycyclic aromatic hydrocarbons (PAH) [29] , polyenes [30][31][32] , organometallics (e.g. metallocenes and metalloporphyrins) [33][34][35][36][37] , quinines [38] , and fullerenes [39] . Van Berkel et al [33,34] were the first to systematically investigate the electrospray ionization of model metalloporphyrins, and observed the molecular ions.…”
Section: Meanwhile According To Reports About Characterization Of Pementioning
confidence: 99%
“…The classes of organic compounds include polycyclic aromatic hydrocarbons (PAH) [29] , polyenes [30][31][32] , organometallics (e.g. metallocenes and metalloporphyrins) [33][34][35][36][37] , quinines [38] , and fullerenes [39] . Van Berkel et al [33,34] were the first to systematically investigate the electrospray ionization of model metalloporphyrins, and observed the molecular ions.…”
Section: Meanwhile According To Reports About Characterization Of Pementioning
confidence: 99%
“…All molecules were optimized with the B3LYP/6‐31G(d) model by using Gaussian 03 suite programs . The B3LYP method was chosen to calculate the selected parameters, which provided accurate measurements at minimum computational cost . Vibrational frequencies indicated that all structures were minima in the potential energy surface.…”
Section: Methodsmentioning
confidence: 99%
“…ESI in combination with MS/MS analysis can be used to elucidate the gas‐phase chemistry of several classes of natural compounds . The number of studies on quinones has increased, because these compounds have interesting electrochemical behavior in the ESI source . The protonated and deprotonated species of 1,4‐naphthoquinone can occur during ESI analysis, and the radical anion has also been detected .…”
mentioning
confidence: 99%
“…The number of studies on quinones has increased, because these compounds have interesting electrochemical behavior in the ESI source . The protonated and deprotonated species of 1,4‐naphthoquinone can occur during ESI analysis, and the radical anion has also been detected . Several papers have described the gas‐phase reactivity of quinonoid compounds by combining ESI studies with computational chemistry .…”
mentioning
confidence: 99%
See 1 more Smart Citation